Altered Expression of Ganglioside Metabolizing Enzymes Results in GM3 Ganglioside Accumulation in Cerebellar Cells of a Mouse Model of Juvenile Neuronal Ceroid Lipofuscinosis - Somogyi, Aleksandra (Int J Mol Sci, 2018)
Juvenile neuronal ceroid lipofuscinosis (JNCL) is caused by mutations in the CLN3 gene. Most JNCL patients exhibit a 1.02 kb genomic deletion removing exons 7 and 8 of this gene, which results in a truncated CLN3 protein carrying an aberrant C-terminus. A genetically accurate mouse model (Cln3(Δex7/8) mice) for this deletion has been generated. Using cerebellar precursor cell lines generated from wildtype and Cln3(Δex7/8) mice, we have here analyzed the consequences of the CLN3 deletion on levels of cellular gangliosides, particularly GM3, GM2, GM1a and GD1a. The levels of GM1a and GD1a were found to be significantly reduced by both biochemical and cytochemical methods. However, quantitative high-performance liquid chromatography analysis revealed a highly significant increase in GM3, suggesting a metabolic blockade in the conversion of GM3 to more complex gangliosides. Quantitative real-time PCR analysis revealed a significant reduction in the transcripts of the interconverting enzymes, especially of β-1,4-N-acetyl-galactosaminyl transferase 1 (GM2 synthase), which is the enzyme converting GM3 to GM2. Thus, our data suggest that the complex a-series gangliosides are reduced in Cln3(Δex7/8) mouse cerebellar precursor cells due to impaired transcription of the genes responsible for their synthesis.